2020
DOI: 10.1111/mec.15532
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the population genetics of partially clonal organisms: When seagrass data meet theoretical expectations

Abstract: Seagrass meadows are among the most important coastal ecosystems in terms of both spatial extent and ecosystem services, but they are also declining worldwide. Understanding the drivers of seagrass meadow dynamics is essential for designing sound management, conservation and restoration strategies. However, poor knowledge of the effect of clonality on the population genetics of natural populations severely limits our understanding of the dynamics and connectivity of meadows. Recent modelling approaches have de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 98 publications
5
32
0
Order By: Relevance
“…In fact, revising the numerous data acquired on clonal plants, including seagrasses, in light of the present results reveals very frequent negative F IS values, suggesting a much higher contribution of clonality than previously thought (Evans et al, 2014; Sinclair et al, 2014; Stoeckel et al, 2006) on the basis of their average R values (see Arnaud‐Haond et al, 2020 for a meta‐analysis). Unfortunately, F IS is often neglected in ecological studies, possibly due to difficulties in disentangling the influence of technical shortcomings such as null alleles from true impacts of reproductive mode (such as selfing).…”
Section: Discussionsupporting
confidence: 51%
“…In fact, revising the numerous data acquired on clonal plants, including seagrasses, in light of the present results reveals very frequent negative F IS values, suggesting a much higher contribution of clonality than previously thought (Evans et al, 2014; Sinclair et al, 2014; Stoeckel et al, 2006) on the basis of their average R values (see Arnaud‐Haond et al, 2020 for a meta‐analysis). Unfortunately, F IS is often neglected in ecological studies, possibly due to difficulties in disentangling the influence of technical shortcomings such as null alleles from true impacts of reproductive mode (such as selfing).…”
Section: Discussionsupporting
confidence: 51%
“…Positive F IS values were observed in all sampled populations, suggesting significant heterozygote deficits. Heterozygote deficits are probably caused by several factors, including inbreeding, linkage disequilibrium, null alleles, recent admixture, and partial clonality [33,34]. In our study, inbreeding and/or recent admixture seemed to be the most likely driver of the positive F IS values, as investigations of Taxus yunnanensis (F IS = 0.228) and Taxus wallichiana (F IS = 0.290) showed prevalent inbreeding [35,36].…”
Section: Population Divergence and Structurementioning
confidence: 48%
“…Signatures of clonality in natural populations are usually inferred from repeated genotypes, along with mean negative values of F IS , and linkage disequilibrium across loci (Balloux et al, 2003; Halkett, et al, 2005). Nevertheless, recent studies reported that one of these signatures, genotypic richness, had poor relevance for measuring the relative importance of sexual versus clonal reproduction (Arnaud‐Haond et al, 2020), even using relatively large sample sizes (from 100 to 500 individuals) (Stoeckel et al, 2020). This is because the estimates of genotypic richness are strongly dependent on sampling strategy and density, basically decreasing with increasing sampling effort (Arnaud‐Haond, Duarte, et al, 2007; Becheler et al, 2017; Gorospe et al, 2015).…”
Section: Discussionmentioning
confidence: 99%